Informational Space of Russia: Between Television Set and the Internet - Yu A Nisnevich (RUDN Journal of Political Science, 2013)
Informational space is one of the main supportive constructions of the modern state. The process of development of infocommunicational infrastructure of Russia that constitutes the framework of its informational space goes in concordance with global trends though with some lag. In the sphere of interaction of the society and public authority in Russia take place content and infocommunicational breaches conditioned by translucency and communicational closeness of Russian authorities. Also there is breakup of the content of mass informing conditioned by breakup between the content about the state of affairs in the country which is being formed by the television and by the Internet with the participation of the users.